Measurement of Patient Satisfaction With the Trend of Virtual Clinics During the COVID-19 Pandemic - Alwabili, Afnan A (Cureus, 2021)
Background The consequences of the coronavirus 2019 (COVID-19) pandemic on healthcare systems worldwide are undeniably disrupting regularly provided care for non-COVID-19 patients. Since the start of the pandemic, medical services in Saudi Arabia have adapted to the situation by providing medical care through virtual clinics. This article aims to evaluate patient satisfaction with virtual clinics during the COVID-19 pandemic. Material and methods A cross-sectional study was conducted among patients who had experience with the virtual clinics of Unaizah College of Medicine, Qassim University, Saudi Arabia. An online questionnaire was sent to all participants who visited the virtual clinic between May 2020 and July 2020. The questionnaire included demographic data and 16 statements to assess patient satisfaction with the virtual clinic experience.  Results A total of 123 participants completed the questionnaire. Their mean age was 33 ± 12 years; 61% were females and 39% were males. Most of the participants were from the Qassim region (77.2%), while 22.8% were from other regions in Saudi Arabia. Dermatology clinics were the most frequently visited virtual clinics, followed by psychiatry clinics. Most of the participants were satisfied with the virtual clinics, with average scores greater than three for most of the components of the questionnaire. Conclusions The participants showed considerable satisfaction for virtual clinics in the time of the COVID-19 pandemic, even though the service was relatively new to them. Future additional efforts will be needed to support clinically appropriate and acceptable virtual visits combined with in-person visits after the pandemic.